Sterility testing of germ-free mouse colonies - Dremova, Olga; Mimmler, Maximilian; Paeslack, Nadja; Khuu, My Phung; Gao, Zhenling; Bosmann, Markus; Garo, Lucien P.; Schön, Nathalie; Mechler, Alexa; Beneich, Yunes; Rebling, Vivian; Mann, Amrit; et al. (Frontiers in Immunology, 2023)
In biomedical research, germ-free and gnotobiotic mouse models enable the mechanistic investigation of microbiota-host interactions and to study their role on (patho)physiology. Throughout any gnotobiotic experiment, standardized and periodic microbiological testing of the defined gnotobiotic housing condition is a key requirement.Here, we review basic principles of germ-free isolator technology, the suitability of various sterilization methods, and the use of sterility testing methods to monitor germfree mouse colonies. We also discuss their effectiveness and limitations, and share the experience with protocols used in our facility. In addition, possible sources of isolator contamination are discussed and an overview of reported contaminants is provided.